STRATEGI PENGELOLAAN KELAS MELALUI PENGUATAN BUDAYA POSITIF SERTA GAME EDUKATIF DI SDN 29 KOTA BIMA - Ramadhan, Syahru; Kusumawati, Yayuk; Khatimah, Nurul; Ma’wiah, Nurul Hikmatul; Pinkan, Pinkan; Yumarna, Yumarna; Yudistirah, Yudistirah (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
Classroom conditions determine the effectiveness of learning activities. To create a learning climate that is not boring for students, teachers must be more creative in implementing classroom management strategies; teachers at SDN 29 Kota Bima so far in implementing classroom management strategies still use inappropriate methods such as giving punishment, disciplining students by telling them to get out of the classroom and others, so that through the application of positive culture and educational games is an essential way in classroom management so that there is no punishment process. Students become more enthusiastic about participating in the learning process. This research uses qualitative research describing events heard and felt and made in narrative or descriptive statements. The data sources in this study were obtained from observations, interviews, and documentation, which were analyzed by data reduction, data presentation, and conclusion drawing. The results showed that applying classroom management strategies through positive culture and educational games is considered effective in creating an exciting and enjoyable learning climate for students. Among its forms are programs that have positive cultural nuances, both nuances of cultivating attitudes, skills, and even knowledge, which are carried out from Monday to Saturday. Teachers have also implemented educational games with positive cultural nuances such as Word Guessing, Singing, and Dancing in the classroom, connecting words and personality drawings.